Flood analysis of Sg. Galas at Dabong, Kelantan by using the HEC-HMS software - Ahmad, Noor Aliza (2004)
Extreme flood cause disasters such as loss of life, property and resources. In Malaysia, the occurrence of floods is due to a lot of factors. One of the major factors is because of the rapid development especially in floodplain area in Lembah Klang and Kuala Lumpur. The increase in the development will automatically increase the impervious area and as the result, the runoff will also increase. This increase will produce more water from the rainfall in the river and this is why flooding happens so often in these areas. If flood can be predicted, control and managed systematically, the losses due to flood can always be prevented or at least minimized. This study focused on the utilization of a computer program called HEC-HMS to estimate the flood discharges for various return periods. The Sungai Galas catchment at Dabong, Kelantan was used as a case study. The total catchment area of Sungai Galas is 3970 km2. Recorded hydrologic data from Sungai Galas basin was used in evaluation and testing of the model. Model evaluation involved calibration and verification. The rainfall and discharge data were obtained from Hydrology and Water Resources Division, the Department of Irrigation and Drainage. Records are available since 1980. Simulation was performed using data from a selected event for calibrating the model parameters. For verification, the model was tested by running the simulation on another storm event. The final output from this model were flood hydrograph for standards storms of return period of 2, 5, 10, 25 and 50 years. The results obtained in this study show that the hydrologic modeling software HEC-HMS can be used to predict flood from the large catchment at Sungai Galas,Dabong